Brazilian guidelines for the pharmacological treatment of pulmonary embolism. Official document of the Brazilian Thoracic Association based on the GRADE methodology - Veronica Moreira Amado; Caio Júlio César dos Santos Fernandes; William Salibe-Filho; Marcelo Basso Gazzana; Ana Thereza Rocha; Hugo Hyung Bok Yoo; Wanderley Marques Bernardo; Suzana Tanni (Jornal Brasileiro de Pneumologia)
ABSTRACT Venous thromboembolism (VTE) is the third most common acute cardiovascular syndrome after acute myocardial infarction and stroke. In recent years, there has been an increase in the incidence of VTE, related to population aging and common comorbidities in the elderly, including chronic cardiorespiratory disease and cancer. On the other hand, disease-related mortality, particularly for pulmonary embolism (PE), shows a decreasing trend, which can be explained by improvements in diagnostic imaging, advances in available therapies, and greater adherence to patient management protocols. The guidelines presented here provide recommendations for the pharmacological treatment of PE in Brazil, on the basis of scientific evidence and with a focus on common practical issues. Six Patient, Intervention, Comparison, and Outcome questions were developed by a group of experts on the topic. Systematic reviews of randomized clinical trials were conducted for each question, with meta-analyses being performed when possible. The level of evidence and strength of recommendation were defined in accordance with the Grading of Recommendations Assessment, Development, and Evaluation approach. With these guidelines, we expect to provide relevant, up-to-date information on the pharmacological treatment of PE.